Social security incidence under uncertainty assessing Italian reforms - Devis Geron (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper analyzes the welfare effects of the Italian social security system in an economy with uncertainty on wages, financial market returns and life expectancy. The introduction of a pension system reproducing the Italian statutory scheme turns out to decrease ex-ante individual welfare, unless restrictions are assumed on retirement behavior. Overall, risk insurance effects of social security play a minor role in determining welfare variations. The new Italian NDC pension system is shown to yield a slight ex-ante welfare improvement from a purely risk-insurance perspective. This relative gain stems from risk diversification across working-life wages in computing benefits.
Keywords: E62; H55; H21; H31; 330; social security reforms; uncertainty; risk insurance; Rentenreform; Sozialversicherung; Lohn; Kapitalertrag; Sterblichkeit; Risiko; Wohlfahrtseffekt; Theorie